Evaluation of the McGill‐Tongji Blended Education Program for Teacher Leaders in General Practice: The importance of partnership and contextualization in International Primary Care Training Initiatives - Ziyue Wang; Xinxin Zhao; Huixia Shen; Hao Wang; Gemma Cheng; Ya Ning Gao; Wenzhen Zuo; Zhuyin Xu; Francesco Avallone; Anish K. Arora; Manxi Guo; Rachel Simmons; et al. (Wiley, 2024)
Abstract Purpose Strong primary health care (PHC) systems require well‐established PHC education systems to enhance the skills of general practitioners (GPs). However, the literature on the experiences of international collaboration in primary care education in low‐ and middle‐income countries remains limited. The purpose of this study was to evaluate the implementation and perceived impact of the McGill‐Tongji Blended Education Program for Teacher Leaders in General Practice (referred to as the "Tongji Program"). Methods In 2020-2021, the McGill Department of Family Medicine (Montreal, Canada) and Tongji University School of Medicine (TUSM, Shanghai, China) jointly implemented the Tongji Program in Shanghai, China to improve the teaching capacity of PHC teachers. We conducted an exploratory longitudinal case study with a mixed methods design for the evaluation. Quantitative (QUAN) data was collected through questionnaire surveys and qualitative (QUAL) data was collected through focus group discussions. Results The evaluation showed that learners in Tongji Program were primarily female GPs (21/22，95%) with less than 4 years of experience in teaching (16/22，73%). This program was considered a successful learning experience by most participants (19/22, 86%) with higher order learning tasks such as critical thinking and problem‐solving. They also agreed that this program helped them feel more prepared to teach (21/22，95%), and developed a positive attitude toward primary care (21/22，95%). The QUAL interview revealed that both the Tongji and McGill organizers noted that TUSM showed strong leadership in organization, education, and coordination. Both students and teachers agreed that by adapting training content into contextualized delivery formats and settings, the Tongji Program successfully overcame language and technology barriers. Conclusions Committed partnerships and contextualization were key to the success of the Tongji Program. Future research should focus on how international primary care education programs affect learners' behavior in their practice settings, and explore barriers and facilitators to change.